Telaah Konsensus Privacy Policy Sebagai Kontrak Digital pada E-Commerce Guna Memberikan Perlindungan Data Pribadi - Salsabila, Elora; Sulistiyono, Adi (Fakultas Hukum Universitas Primagraha, 2024)
This research is motivated by the phenomenon of personal data misuse occurring in various e-commerce platform. E-commerce platforms inherently have the authority and full responsibility over the collection, processing, and utilization of personal data through profiling activities. The policy regarding these activities is regulated an included in the digital agreement document called the “Policy Privacy”. This study aims to examine whether the “Privacy Policy” has obtained sufficient validity of agreement form e-commerce service users, considering the consensus given appears to be coercive. Moreover, many clauses in these